REPRESENTATION OF TURKISH MYTHOLOGY IN VIRTUAL REALITY ENVIRONMENT - UCAN, Bahadir; TOY, Ertan; KAHRAMAN, Mehmet Emin; GULACTI, Ismail Erim (PEOPLE: International Journal of Social Sciences, 2020)
In this research, it is aimed to represent the elements in oral and written traditions such as mythology, epic and story on the virtual reality environment. Mythology has always been used for generating visual design elements. As an example, Miyazaki’s cartoons are great examples of Japan mythology-based character designs. There are also many cartoon and film products of Greek mythology. In contrast, despite rich visual contents of Turkish mythology, Turkish mythological elements aren’t used sufficiently for visual design or analyzed scientifically in detail. By this research, the world’s first Turkish mythology museum in a virtual environment is established. For this purpose, a literature review is conducted on gathering related information on Turkish mythology and elements of Turkish mythology are transferred into visual design units. Models and designs are created on Blender 2.80 and Autodesk 3dsmax 2019. Unity Hub is used for extended reality interaction. Within the scope of the research, augmented reality future is added to character designs created by using mythological characters. With augmented reality, models gained a feature that enables interactive participation of audience over phone/tablet. This research has been supported by Yildiz Technical University Scientific Research Projects Coordination Department. Project Number: SBA-2019-3749 Augmented Reality Applications Using Three Dimensional Models.